Modifying the cancer-immune set point using vaccinia virus expressing re-designed interleukin-2. Issue 1 (December 2018) - Liu, Zuqiang; Ge, Yan; Wang, Haiyan; Ma, Congrong; Feist, Mathilde; Ju, Songguang; Guo, Z.; Bartlett, David
Abstract The complex immune tumour microenvironment requires an equally complex immunotherapy approach, especially when the cancer-immune set point is non-inflamed. Oncolytic viruses expressing immune activating cytokines might optimally modify the immune microenvironment and improve the antitumour effects. In this study, we have explored a variety of IL-2 constructs expressed by a tumour-selective oncolytic vaccinia virus, designed to maintain IL-2 in the tumour microenvironment to reduce systemic toxicity. An IL-2 construct combining a glycosylphosphatidylinositol (GPI) anchor with a rigid peptide linker leads to functional IL-2 expression on the tumour cell surface and in the tumour microenvironment. This virus construct effectively modifies the cancer-immune set point and treats a variety of murine tumour models with no toxic side effects. In combination with PD-1/PD-L1 blockade this virus cures most of the mice with a high tumour burden. This combination represents a treatment for cancers which are to date unresponsive to immunotherapy. IL-2 is used systemically for cancer therapy but it is associated with severe toxicity. Here, the authors design a recombinant vaccinia virus expressing membrane-bound IL-2 that shows therapeutic efficacy alone or in combination with checkpoint inhibitors in colon cancer-bearing mice.